1994
DOI: 10.1021/bi00208a011
|View full text |Cite
|
Sign up to set email alerts
|

Proton Linkage in Formation of the Cytochrome c-Cytochrome c Peroxidase Complex: Electrostatic Properties of the High- and Low-Affinity Cytochrome Binding Sites on the Peroxidase

Abstract: The electrostatic character of cytochrome c-cytochrome c peroxidase complex formation has been studied by potentiometric titration between pH 5.5 and 7.75. Potentiometric data obtained at ionic strength > or = 100 mM were adequately analyzed in terms of 1:1 complex formation while the simplest model capable of fitting similar data obtained at lower ionic strength involves the assumption of two inequivalent binding sites for the cytochrome on the peroxidase. The stability of cytochrome c binding at the high-aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
110
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(129 citation statements)
references
References 29 publications
17
110
2
Order By: Relevance
“…c, activity first increases with ionic strength and then decreases. Such complex behavior has been interpreted as an ionic strengthdependent change in the rate-limiting step (30) as well as a multisite model with CCP having both high-affinity and lowaffinity sites (8,(10)(11)(12). As shown in Table 2, the complex is essentially inactive (exhibits Ͻ7.2% activity compared with wild type) toward both substrates at low and high ionic strengths.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…c, activity first increases with ionic strength and then decreases. Such complex behavior has been interpreted as an ionic strengthdependent change in the rate-limiting step (30) as well as a multisite model with CCP having both high-affinity and lowaffinity sites (8,(10)(11)(12). As shown in Table 2, the complex is essentially inactive (exhibits Ͻ7.2% activity compared with wild type) toward both substrates at low and high ionic strengths.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, several investigations using a variety of methods indicate two cyt. c binding sites (8)(9)(10)(11)(12), although less clear is whether both sites are productive in electron transfer of physiological relevance.…”
mentioning
confidence: 99%
“…For example, although the affinity of Mn 2ϩ binding to the Mb double variant is Ϸ20-fold greater at the newly created site than at the endogenous metal ion binding site, the affinity of the peroxidase for Mn 2ϩ is about two orders of magnitude greater (29). Interestingly, however, the affinity of the peroxidase for Mn 2ϩ at acidic pH, where catalytic activity of the enzyme is greatest, is the same order of magnitude as that for the variant studied here.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of Mn 2ϩ ions to wild-type Mb and the variant was studied by monitoring the release of protons upon metal ion binding. Instrumentation (27), preparation of metal ion solutions (28), and data acquisition and analysis procedures (28,29) were reported previously. The dependence of peroxidase activity on pH was evaluated at 25°C between pH 5.0 and 8.0 with a mixed buffer system (5 mM Mes͞5 mM Mops͞5 mM TAPS͞95 mM NaCl) [ (32).…”
Section: Methodsmentioning
confidence: 99%
“…Using recombinant LmP and LmCytc, we found that the steady-state kinetics of the Lm system is far simpler than the yeast system (5). First, the Lm system obeys straightforward Michaelis-Menten kinetics, whereas yeast CCP does not (20) possibly because yeast CCP has a second weak site for Cytc (21,22). Second, LmP exhibits a steady decrease in activity with increasing ionic strength (5), whereas yeast CCP activity increases with ionic strength up to ∼100 mM and then decreases (20).…”
mentioning
confidence: 99%